OC-060 Colonoscopy versus ctc in the north central london bowel cancer screening programme. (17th June 2017) - Fawkes, J; Corpus, M; Stein, J; Smith, T; Andrew, P; Vega, R; Seward, E
Abstract : Introduction: Colonoscopy is the gold standard investigation for bowel cancer screening (BCS), however in cases of severe comorbidity, CT colonography (CTC) is offered. Our BCS service has been identified as a high referrer for CTC. This study aims to identify the criteria for indicating CT colonography in a consecutive cohort of patients with FOB+ within our BCS program. It also describes and compares the diagnostic findings at colonoscopy and CTC within our program. Method: All new patients screened over a 12 month period were included, except those with a history of polyps on a surveillance pathway. The clinical justification for CTC was reviewed from imaging requests, and also minutes from weekly clinical review meetings where every patient not undergoing colonoscopy are discussed. Diagnostic yield for adenocarcinoma, high, intermediate and low risk adenomas for CTC and colonoscopy were compared using a Pearson's chi-squared or Fisher's exact test as appropriate, significance p<0.05. Results: 779 patients were included. 94 (12.1%) underwent CTC. Of these, 26 (27.7%) because of anticoagulation, 39 (41.5%) with cardiac comorbidity (arrhythmias, angina, infarct, aortic stenosis, uncontrolled hypertension, aortic aneurysm), 9 (9.6%) with respiratory comorbidity (COPD, pulmonary oedema), 8 (8.5%) had advanced cancer, 5 (5.3%) liver cirrhosis, 9 (9.6%) severe chronic kidney disease, 15 (16%) were post CVA or had impaired mobility, and 3 (3.2%) 'other' (dementia, failed previous colonoscopy). 6 (6.4%) of patients expressed a preference for CTC. Two (2.1%) of the patients undergoing CTC compared to 33 (4.8%) undergoing colonoscopy were found to have cancer (p>0.05). 25 (27.7%) patients at CT were found to have polyps next to 336 (49.1%) at colonoscopy (significant p<0.01). Of these, high risk polyps were found in 1 case (1.1%) at CT, and 62 cases (9.1%) at colonoscopy (significant to p<0.01), intermediate risk polyps in 10 (10.6%) at CT, and 86 (12.6%) at colonoscopy (not significant), and low risk polyps in 13 (13.8%) of cases at CT and 188 (27.5%) at colonoscopy (significant p<0.01). Conclusion: Our data shows there is significant comorbidity in the population referred for CTC. There is a significantly lower level of polyp detection in patients screened by CTC, in keeping with the published national data. A significantly higher amount of CTCs do not find any pathology. Our 12% referral rate to CTC is high compared to national averages cited at 2%>9%, however, CTC gives consideration to the risks of colonoscopy stated in the literature. There are no national guidelines for CTC over colonoscopy, leaving room for subjective interpretation of appropriateness. Only a minority of our CTCs are patient preference, and even these are acceptable if the alternative is no engagement with the BCSP. Disclosure of Interest: None Declared